2018
DOI: 10.1371/journal.pntd.0006755
|View full text |Cite
|
Sign up to set email alerts
|

Health preparedness plan for dengue detection during the 2020 summer Olympic and Paralympic games in Tokyo

Abstract: BackgroundParticipants in mass gathering events are at risk of acquiring imported and locally endemic infectious diseases. The 2014 dengue outbreak in Tokyo gathered attention since it was the first time in 70 years for Japan to experience an autochthonous transmission. Preparation for emerging infectious threats is essential even in places where these outbreaks have been largely unknown. The aim of this study is to identify strategies for early detection and prevention of dengue infection during the 2020 summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 29 publications
0
14
1
Order By: Relevance
“…The next results of this study showed that there was no relationship between endemicity status and the preparedness of health workers in dealing with DHF outbreaks in Banda Aceh City (P = 0.838). The results of this study are different from the opinions expressed by Yanagisawa, Wada, Spengler, & Sanchez-Pina [36] namely the preparation for the emergence of the threat of infection is very important given the nature of infectious DHF disease. The pragmatic approach that must be taken is to have a preparedness plan so that health workers together with the community know how to recognize the symptoms and how to respond.…”
Section: Discussioncontrasting
confidence: 99%
“…The next results of this study showed that there was no relationship between endemicity status and the preparedness of health workers in dealing with DHF outbreaks in Banda Aceh City (P = 0.838). The results of this study are different from the opinions expressed by Yanagisawa, Wada, Spengler, & Sanchez-Pina [36] namely the preparation for the emergence of the threat of infection is very important given the nature of infectious DHF disease. The pragmatic approach that must be taken is to have a preparedness plan so that health workers together with the community know how to recognize the symptoms and how to respond.…”
Section: Discussioncontrasting
confidence: 99%
“…The large number of responses obtained in one month suggests that the method we used can garner useful information about travel and travel health risks not only for China, but, by extension, for any other geographic region. Such results allow the regionally-targeted dissemination of warnings about weather conditions, natural disasters (cyclones, earthquakes, tsunamis, typhoons, hurricanes, avalanches), epidemics, [23][24][25] civil unrest, 26 water safety, 27 altitude, 28 air quality, 29 local drug use laws, 30 mass gatherings such as large-scale religious events, [31][32][33] sports events, 34 and open air music festivals that breed outbreaks of communicable disease, accidents, violent assaults, and infrastructure breakdowns, 35 and inform travelers about geographic pockets of inadequate or unsafe health service availability. Time-targeted messaging can be applied to different world regions as mass travel occurs at different times in different countries.…”
Section: Discussionmentioning
confidence: 99%
“…albopictus, which leads to reduced occurrence of autochthonous infections in a view of ANOVA. Furthermore, Yanagisawa et al (6) suggested the reinforcement of early detection of dengue infection to prevent further transmission in the Olympiad.…”
Section: )mentioning
confidence: 99%
“…A lot of participants and spectators from abroad will visit Tokyo during this season. Therefore, introduction of dengue virus (DENV) is highly possible, and the risk of outbreak of autochthonous dengue fever will build up (6,7).…”
Section: Introductionmentioning
confidence: 99%